Dual-Mode Chained-Response Dual-Band Filter - Ng, G.S. (Institute of Electrical and Electronics Engineers Inc., 2021)
Chained-response multiband filters offer flexibility in selecting inner-band frequency and bandwidth for each passband which improves the integration of wireless applications into one multiband system. In space applications, dual-mode multiband filters are usually employed due to size and weight reduction. Waveguide filters have low loss and high power handling which makes them suitable to be deployed in space applications. However, the waveguide filter is bulky and heavy, and thus, miniaturization of the filter is crucial. In this paper, a dual-mode dual-band chained-response filter is designed and presented. A three dual-mode cavities rectangular waveguide filter with center frequencies 3.8 GHz and 4 GHz is simulated to verify the design. Â© 2021 IEEE.